2020
DOI: 10.1002/jat.3998
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of low‐density lipoprotein receptor class A domain‐containing protein 4 (Ldlrad4) in the liver of rats treated with nongenotoxic hepatocarcinogen to induce transforming growth factor β signaling promoting cell proliferation and suppressing apoptosis in early hepatocarcinogenesis

Abstract: We previously found downregulation of low-density lipoprotein receptor class A domain-containing protein 4 (LDLRAD4), a negative regulator of transforming growth factor (TGF)-β signaling, in glutathione S-transferase placental form (GST-P) expressing (+) pre-neoplastic lesions produced by treatment with nongenotoxic hepatocarcinogens for up to 90 days in rats. Here, we investigated the relationship between LDLRAD4 downregulation and TGFβ signaling in nongenotoxic hepatocarcinogenesis. The transcripts of Tgfb a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…MAPK signaling pathway is also important in regulating feather growth and development ( Ji et al, 2021 ). Ito et al (2020) found that downregulation of LDLRAD4 induces transforming growth factor β signaling, promoting cell proliferation and suppressing apoptosis. These results also suggest that DDX10 and LDLRAD4 genes play an important role in feather maturation.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling pathway is also important in regulating feather growth and development ( Ji et al, 2021 ). Ito et al (2020) found that downregulation of LDLRAD4 induces transforming growth factor β signaling, promoting cell proliferation and suppressing apoptosis. These results also suggest that DDX10 and LDLRAD4 genes play an important role in feather maturation.…”
Section: Discussionmentioning
confidence: 99%